Mathematics-Integration

posted by Shenaya

Question:
Prove that [integrate {x*sin2x*sin[π/2*cos x]} dx] /(2x-π) } from (0-π)
= [ integrate {sin x*cos x*sin[π/2*cos x} dx ] from (0-π).

My thoughts on the question:

We know that integrate f(x) dx from (0-a) = integrate f(a-x) dx from (0-a)

From that and by sin(2x)=2sin(x)*cos(x)

L.H.S. = integrate { (π-x)*2sin(π-x)*cos(π-x)*sin[(π/2)cos(π-x)] dx] /[2(π-x) - x]}from (0-π)
= integrate { [ (π-x)*2sinx*cosx *[ sin(π/2*coss x] dx ]/(π-2x)} from (0-π)
= integrate { [(π-x) 2sinx*cosx*[sin(π/2*cosx] dx/(π-2x) } from (0-π)

But in the result they are asking is to prove,there's no "2" and terms of (π-x) and (π-2x)

1. Shenaya

pi is displayed as a question mark here.

2. MathMate

I see π being properly displayed probably due to encoding.

I also see that there is a removable discontinuity at x=π/2.

Numerical integration (skipping x=π/2) gives identical results for both expressions, so hopefully no typo.
Try translating limits to (-π/2, π/2).

3. Shenaya

I've heard about "numerical integration" but we haven't been taught that.So I should solve this without using that method.

Similar Questions

1. calc

Where do I start to prove this identity: sinx/cosx= 1-cos2x/sin2x please help!! Hint: Fractions are evil. Get rid of them. Well, cos2x = cos 2 x - sin 2 x, so 1-coscx = 1 - cos 2 x - sin 2 x = 1 - cos 2 x + sin 2 x You should be able …
2. tigonometry

expres the following as sums and differences of sines or cosines cos8t * sin2t sin(a+b) = sin(a)cos(b) + cos(a)sin(b) replacing by by -b and using that cos(-b)= cos(b) sin(-b)= -sin(b) gives: sin(a-b) = sin(a)cos(b) - cos(a)sin(b) …
3. Integral calculus

Please can anyone help with the following problems - thanks. 1) Integrate X^4 e^x dx 2) Integrate Cos^5(x) dx 3) Integrate Cos^n(x) dx 4) Integrate e^(ax)Sinbx dx 5) Integrate 5xCos3x dx The standard way to solve most of these integrals …
4. calculus

1) Integrate Cos^n(x) dx 2) Integrate e^(ax)Sinbx dx 3) Integrate (5xCos3x) dx I Will be happy to critique your thinking on these. 1) Derive a recursive relation. 2) Simplest by replacing sin(bx) by Exp[i b x] and taking imaginary …
5. calc

find the area between the x-axis and the graph of the given function over the given interval: y = sqrt(9-x^2) over [-3,3] you need to do integration from -3 to 3. First you find the anti-derivative when you find the anti-derivative …
6. Mathematics - Trigonometric Identities

Let y represent theta Prove: 1 + 1/tan^2y = 1/sin^2y My Answer: LS: = 1 + 1/tan^2y = (sin^2y + cos^2y) + 1 /(sin^2y/cos^2y) = (sin^2y + cos^2y) + 1 x (cos^2y/sin^2y) = (sin^2y + cos^2y) + (sin^2y + cos^2y) (cos^2y/sin^2y) = (sin^2y …
7. TRIG!

Posted by hayden on Monday, February 23, 2009 at 4:05pm. sin^6 x + cos^6 x=1 - (3/4)sin^2 2x work on one side only! Responses Trig please help! - Reiny, Monday, February 23, 2009 at 4:27pm LS looks like the sum of cubes sin^6 x + cos^6 …